Rahasia sukses: implementasi manajemen strategi dalam perbankan syariah - Wahono, Dava Wahyu (Maliki Interdisciplinary Journal, 2025)
This study explores the implementation of strategic management in Islamic banking as a key factor in enhancing competitiveness and sustainability within Islamic financial institutions. The research focuses on four main strategic aspects: leadership commitment, human resource competence, digital technology utilization, and the development of Sharia-compliant products and services. Through literature reviews and case analyses of several Islamic banks in Indonesia, the study finds that successful strategic management relies heavily on the synergy between Sharia governance, technological innovation, and an ethical organizational culture oriented toward public welfare. The integration of digitalization with Islamic values has proven effective in improving efficiency, transparency, and customer trust. Therefore, effective strategic management not only strengthens the competitive position of Islamic banks but also contributes to building a fair and sustainable financial system.